Kesulitan belajar matematika pada mahasiswa pgsd - Lidia Evi; Lusia Mimi Febrianti; Ilmawati Fahmi Imron (Institut Pendidikan Indonesia, 2023)
Difficulty in learning mathematics is a condition where there is a deviation between the actual abilities possessed and the achievements shown which are manifested in three basic academic areas such as reading, writing and arithmetic. The purpose of this study was to determine students' difficulties in learning mathematics and the factors that cause difficulties for students in learning mathematics. This type of research is research using a qualitative approach, which is a process of research and understanding based on a methodology that investigates a difficulty in learning mathematics. The data collection technique uses a questionnaire. The subjects of this study were ten students of PGSD UNP Kediri. Based on the results of the study, the learning difficulties factor for students consisted of 5 factors, namely factors of low basic mathematical ability, the factor of not paying attention to the explanation of the material properly, the factor of drowsiness, the factor of not like learning Mathematics, the factor of playing HP when learning takes place, and time factor. Kesulitan belajar matematika adalah suatu kondisi terjadinya penyimpangan antara kemampuan sebenarnya dimiliki dengan prestasi yang ditunjukkan yang termaniferstasi pada tiga bidang akademik dasar seperti membaca, menulis, dan berhitung. Tujuan dari penelitian ini adalah untuk mengetahui kesulitan siswa dalam belajar matematika dan faktor-faktor yang menimbulkan kesulitan bagi siswa dalam mempelajari matematika. Jenis penelitian ini adalah penelitian dengan menggunakan pendekatan kualitatif, yang merupakan suatu proses penelitian dan pemahaman yang berdasarkan pada metodologi yang menyelidiki suatu kesulitan dalam pembelajaran matematika.Teknik pengumpulan data menggunakan kuisioner. Subjek penelitian ini adalah 15 mahasiswa PGSD UNP Kediri. Berdasarkan hasil penelitian faktor kesulitan belajar mahasiswa terdiri dari 6 faktor yaitu: Faktor kemampuan dasar matematika rendah, Faktor tidak memperhatikan penjelasan materi dengan baik, Faktor mengantuk, Faktor tidak menyukai pembelajaran Matematika, Faktor bermain HP saat pembelajaran berlangsung, dan Faktor waktu/jam.